Implementasi Kebijakan Pengelolaan Pariwisata Berkelanjutan Dalam Peningkatan Potensi Ekonomi Di Kabupaten Sinjai - Jusniaty, Jusniaty; Baharuddin, Baharuddin; Nurmiati, Nurmiati; Muh. Alfi Syahrin (Program Studi Administrasi Publik, 2025)
The existing policies provide clear direction for organizations or governments to achieve desired results, especially in the tourism sector. Policy implementation is the final step of the policy process. The rule implementation process is the final and most significant determinant of overall policymaking. Implementation aims to build a network to open up opportunities where public policy objectives are realized through government organizations involving various interested parties in an activity agenda, such as the tourism sector. For this reason, the theory used to conduct this study is Edward III's policy implementation theory. Based on this theory, the success of policy implementation is determined by four factors: communication, resources, disposition, and bureaucratic structure.